Analysis Of The Effect Of Stock Returns Using The Capital Asset Pricing Model (Capm) Method On Risk In Food And Beverage Companies Listed On The Idx For The 2020-2022 Period - Noviana Ramadhani; Vika Triya Wahyuni; Naula Chantika Putri F; Maria Yovita R.Pandin (Publikasi Inspirasi Indonesia, 2023)
This study aims to determine whether the stock return obtained from the CAPM calculation can significantly affect the risk of food and beverage companies listed on the Indonesia Stock Exchange for the period 2020–2022. The variables used in this study are risk as an independent variable or independent variable calculated using the Beta (β) formula, and stock returns as a dependent variable or dependent variable calculated using the CAPM formula. This study uses a descriptive statistical analysis test, a classical assumption test, and a partial t hypothesis test. The results of this study indicate that the stock return variable significantly affects the risk variable because the sig value is 0.004 ˂ 0.05, which means Ho is rejected and Ha is accepted, which means that the effect of the independent variable on the dependent variable is unidirectional. This shows that the higher the level of return expected by investors, the higher the level of risk that investors will take. This is in accordance with the portfolio theory in the CAPM method, which suggests that there is a positive and linear relationship between beta, risk, and the expected rate of return.